Immunohistochemical expression and prognostic value of PD-L1 in Extrapulmonary small cell carcinoma: a single institution experience. Issue 1 (29th May 2018) - Salhab, Mohammed; Migdady, Yazan; Donahue, Melanie; Xiong, Yiqin; Dresser, Karen; Walsh, William; Chen, Benjamin J.; Liebmann, James
Abstract : Background: Extrapulmonary small cell carcinomas (ESCC) are rare but aggressive tumors. Relapses are common despite treatment with chemotherapy and/or radiotherapy. Prospective data for treatment of ESCC are lacking; treatment of these cancers usually incorporates lung small cell carcinoma treatment recommendations. Cancer staging remains the most important prognostic factor. Cancer immunotherapy targeting the PD-1/PD-L1 pathway has shown efficacy in multiple tumor types, and could be an appealing treatment strategy for these rare tumors. Methods: We investigated PD-L1 expression by immunochemistry (IHC) in ESCCs diagnosed at University of Massachusetts Medical Center, from 1999 to 2016. 34 cases with sufficient material were selected for PD-L1 IHC analysis using clone E1L3N. PD-L1 expression was evaluated using the combined positive score (CPS). Retrospective chart review was performed. We evaluated the incidence and prognostic value of PD-L1 expression in ESCC at our institution. Results: Twelve out 34 cases (35%) had PD-L1 CPS scores ≥1. Ten cases had CPS scores ranging 1–5, whereas 2 cases had CPS scores > 80. The overall response rate to the standard chemotherapy with/without radiotherapy in the PD-L1 positive group was 80% versus 67% for the PDL-1 negative group ( p -value 0.67). The median overall survival for the PD-L1 positive group, regardless of stage, was 11.5 months versus 7 months for PD-L1 negative group ( p -value 0.34). Patients with limited stage disease with positive PD-L1 had a median survival of 53 months compared to 15 months for patients with PD-L1 negative limited stage ( p -value 0.80). Conclusions: This study showed that at least one third of our ESCC tissue samples expressed PD-L1. There was a trend for higher response rates to the standard chemotherapy with/without radiotherapy and improved survival in PD-L1 positive patients. Further studies are required to understand the implications of immune dysregulation in these aggressive tumors. PD-L1/PD-1 inhibitors should be investigated in this group of patients.